MENINGKATKAN ABSTINENCE SELF EFFICACY RESIDEN MELALUI KONSELING KELOMPOK PENDEKATAN RATIONAL EMOTIVE BEHAVIOR TEKNIK ROLE PLAYING - Adelia Oky Setya Pratiwi; Mungin Eddy Wibowo (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
Rehabilitation is a guarantee of treatment from the Indonesian government to help recover drug addicts from using drugs again (Dewan, 2012). In fact, there are still many residen after undergoing rehabilitation who experience relapse due to their belief in their ability to refuse to use drugs again or called self-efficacy abstinence is low (Tuapattinaja, Irmawati, Saragih, 2016). This study aims to determine the effectiveness of group counseling with rational emotive behavior approach role playing technique to increase abstinence self-efficacy of residen. This type of research is an experiment with a one-group pretest-posttest design. The subjects of this study were five residen who were selected using purposive sampling technique. The data was collected using the drug avoidance self-efficacy scale (DASES) and analyzed by the Wilcoxon matched pairs. The results showed that there was a significant increase in the abstinence self-efficacy of residen (Z = -2.032, P0.05). The conclusion of this study is group counseling with rational emotive behavior approach role playing technique effective in increasing abstinence self-efficacy of residen.